An analytical approach to assess the current state of a roadmap - Ronald S. Vatananan (2018)
Technology Roadmapping (TRM) has become the method of choice for practitioners to develop a strategic plan linking business strategy, product development, technology, and R & D activities. Keeping a roadmapping operation alive is considered a major challenge. One element of sustaining a roadmapping process is to be aware of when the process needs to be reviewed. A review entails maintaining a roadmap by including up-to-date information, as well as updating or revising its strategic targets. To assist this decision making an analytical approach along with an evaluation model is proposed that can analyze the impact from changes in key drivers and their collective effect on a roadmap. The proposed analytical approach and evaluation model are used to operationalize the maintenance process of a roadmap and serve as a mechanism to sustain a roadmap implementation. The evaluation model produces a TRM status signal to indicate the current state of an organization's roadmap. Management can then use the TRM status signal to recommend appropriate responses for reviewing their roadmap (i.e. maintaining, updating or revising). © 2011 IEEE.